Indirect implications of COVID-19 prevention strategies on non-communicable diseases: An Opinion Paper of the European Society of Hypertension Working Group on Hypertension and Cardiovascular Risk Assessment in Subjects Living in or Emigrating from Low Resource Settings - Modesti, Pietro A.; Wang, Jiguang; Damasceno, Albertino; Agyemang, Charles; Van Bortel, Luc; Persu, Alexandre; Zhao, Dong; Jarraya, Faical; Marzotti, Ilaria; Bamoshmoosh, Mohamed; Parati, Gianfranco; Schutte, Aletta E. (BMC medicine, 2020)
After its outbreak in China, the novel COronaVIrus Disease 19 is spreading across the globe. It is an emergency the world has never seen before. The attention of health systems is mainly focused on COronaVIrus Disease 19 patients and on the risk that intensive care units might be overwhelmed by the serious pulmonary complications. Different countries are also attempting to establish infection prevention and control strategies which proved effective in China where the outbreak was initially reported. We reflect on important lessons to be learnt from different countries. The effects that infection prevention and control strategies, such as social distancing or isolation, can have on the care of millions of patients with non-communicable diseases, who may be indirectly affected, have not been taken into consideration so much. When dealing with COronaVIrus Disease 19, policy makers and healthcare personnel should consider the indirect effects on the treatment of non-communicable diseases.